EVALUATION OF ANTICANCER ACTIVITY (HCC) IN NELUMBO NUCIFERA (NELUMBONACEAE) FLOWER EXTRACT BY INVITRO SCREENING METHOD - THIRUNAVUKARASU A, JASWINBENITTA R, ABINAYA N, PRADEESHWAR K M, VIJAY ANANTH V (South Eastern European Journal of Public Health, 2025)
Nelumbo Nucifera, a revered traditional medicine has been scientifically investigated for its potential therapeutic application in treating Hepatocellular Carcinoma (HCC), a devastating form of liver cancer. A Comprehensive phytochemical analysis revealed the presence of an array of bioactive compounds, including alkaloids, flavonoids, polyphenols, tannins and terpenoids. The extract demonstrated an impressive spectrum of biological activities, encompassing enhanced cell viability, potent antiproliferative effects, robust antioxidant properties and significant anti-inflammatory activity. The antioxidant efficacy was meticulously evaluate using the DPPH (2,2 diphenyl-1-picrylhydrazyl) method, while the DLA (Dalton’s Lymphoma assay) method was employed to investigate apoptotic cell death. Additionally, the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was used to evaluate the cytotoxicity, proliferation, and viability of (Hepg2-cell line) cells. The extracts potential anti-HCC activity was rigorously analyzed using UV spectrophotometry (200-400nm) and quality control tests, including thin – layer chromatography (TLC). This study provides compelling statistical data supporting the therapeutic potential of Nelumbo Nucifera against HCC, underscoring its promise as a novel adjunctive treatment strategy for this debilitating disease.